Cardiac Rehabilitation Program with High Intensity Aerobic Exercise Can Reverse Diastolic Impairment in Patients Undergoing Coronary Artery Bypass Surgery: - Rai, Alireza; Bahremand, Mostafa; Salehi, Nahid; Rezaee, Mansour; Raeisei, Ahmad Ali (Galen Medical Journal, 2014)
Background: Cardiac rehabilitation is known as a powerful non-pharmacological approach for improving functional capacity, and left ventricular systolic function; however, some limited data have suggested an attenuation of the decline in diastolic function with this program. This study investigated the effect of high intensity aerobic exercise following coronary artery bypass surgery (CABG) on diastolic dysfunction. Materials and Methods: Forty four patients with different levels of diastolic dysfunction who underwent CABG surgery were included. The participants attended the complete cardiac rehabilitation program three times per week for two months (totally 24 sessions). The patients underwent complete transthoracic echocardiographic studies including two-dimensional and spectral Doppler echocardiography immediately before attending rehabilitation program and also after the completion of rehabilitation sessions. Results: There was a significant decrease of isovolumic relaxation time (IVRT) after participating complete cardiac rehabilitation (94.0 to 89.0; P=0.001). The diastolic function parameters of early diastolic mitral inflow peak velocity to late diastolic mitral inflow peak velocity (E/A) ratio (0.94 to 1.04; P=0.001), deceleration time (DT) of the mitral E wave (192.7 to 219.0; P=0.011), and velocity of early diastolic mitral annular motion (Ea) (5.9 to 6.7; P=0.026) were improved after the rehabilitation, whereas mitral A duration to pulmonary A duration (MAD/PAD) ratio was slightly improved (1.07 to 1.12; P=0.056) and pulmonary veins systolic flow to pulmonary vein diastolic flow (PVS/PVD) ratio (0.89 to 1.04; P=0.345) remained unchanged. Conclusion: A complete cardiac rehabilitation program with high intensity aerobic exercise approach can reverse diastolic impairment in patients undergoing CABG.